Eficácia de um dentifrício contendo partículas clareadoras no tratamento da descoloração dentária: ensaio clínico randomizado - Sousa, Jossaria Pereira de (2013)
The aim of this clinical trial was to evaluate the efficacy, safety and acceptability of whitening toothpaste containing blue covarine in the treatment of tooth discoloration. It is a parallel controlled double-blind randomized clinical trial which followed the guidelines published by CONSORT. Seventy-five subjects with shade mean C1 or darker for the six maxillary anterior teeth were randomized in three treatment groups (n= 25): G1- conventional fluoridated toothpaste, G2- whitening toothpaste containing a silica system and blue covarine, and G3- bleaching with 10% carbamide peroxide. Subjects from G1 and G2 were instructed to brush their teeth for 90 seconds, twice per day during 2 weeks. Subjects from G3 used 10% carbamide peroxide gel in a tray for 4h/night also for two weeks. Shade evaluations were done with a spectrophotometer (Vita Easyshade® Advance) at baseline, after first application and at 2 and 4 weeks. Subjects perception about tooth color appearance was assessed by a visual analog scale (VAS). Tooth sensitivity (TS) and gingival irritation (GI) were measured daily using a scale ranging from 1 (no sensitivity) to 5 (severe sensitivity) during three weeks, and the acceptability of products was measured with a questionnaire that included questions about subjects opinion regarding the treatment regimen. At all evaluations periods, there was not statistical difference between G1 and G2 groups considering the CIEL*a*b* color parameters (p> 0.3) or the tooth shade means (p> 0.7). At 2-week evaluation, ΔE* value for G3 was statistically higher (9.2) than for G1 (2.3) and G2 (2.1) (p= 0.0001). G1 and G2 reported a major dissatisfaction with tooth color appearance than G3 (p= 0.0001).Tooth sensitivity and gingival irritation were reported by 12% of subjects from G2, while the same symptoms were perceived by 84% and 80% of G3. At first and second weeks of treatment, G2 experienced tooth sensitivity and gingival irritation similarly to G1 group and statistically lower than G3 (p< 0.01). It was observed a negative correlation between TS/GI and day of evaluation (r= -0.08 and r= -0.91) in G3. Within the limitations of this study, it could be concluded that the whitening toothpaste containing a silica system and blue covarine resulted in no significant changes on tooth color, as the conventional toothpaste. These groups did not show whitening effect as the group treated with 10% carbamide peroxide. However, all could be considered safe and acceptable to be used daily for a short term.